Dasar Laut Sinusoidal Sebagai Reflektor Gelombang - Noviantri, Viska (Bina Nusantara University, 2011)
This article discusses about the influence of sinusoidal sandbars towards the amplitude of incident wave. sinusoidal sandbars may lead to Bragg resonance. Basically, when a wave meets a different depth, it will scatter into a transmitted wave and a reflected wave. Bragg resonance happens when the wavelength of incident wave is twice of the wavelength of the periodic bottom disturbance. We apply the multi-scale asymptotic expansion to obtain the results. Eventually we find that a larger amplitude disturbance leads to larger reflected wave amplitude. This result explains that the sinusoidal sandbars indeed can reduce the amplitude of incident wave and protect a beach from large amplitude incident waves.